(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A crucial first step in raising port productivity, enhancing service delivery, and guaranteeing greater integration with neighboring sectors is the accurate and scientific assessment of port performance. In this study, a novel approach to the multi-criteria decision analysis (MCDA) paradigm is presented. Our new approach’s key characteristic is that it uses partially ordered sets, whose components are structured from a relational viewpoint rather than a computational one as in earlier approaches. We will also examine the current state of Egyptian ports in this study and assess them using the suggested methodology. The suggested strategy yielded outstanding computational results for analyzing 12 Egyptian ports. Furthermore, this study advances the strategic knowledge of how operational features and infrastructure affect port performance in developing nations. It provides a repeatable framework for decision-makers seeking to prioritize investments, boost port competitiveness, and promote sustainable economic growth through increased maritime logistics efficiency by utilizing a data-driven, multi-criteria evaluation methodology.